Genetic algorithms for the scheduling in additive manufacturing - S. Castillo-Rivera; J. De Antón; R. del Olmo; J. Pajares; A. López-Paredes (International Journal of Production Management and Engineering)
Genetic Algorithms (GAs) are introduced to tackle the packing problem. The scheduling in Additive Manufacturing (AM) is also dealt with to set up a managed market, called “Lonja3D”. This will enable to determine an alternative tool through the combinatorial auctions, wherein the customers will be able to purchase the products at the best prices from the manufacturers. Moreover, the manufacturers will be able to optimize the production capacity and to decrease the operating costs in each case.